The genus Mallacoota (Crustacea, Amphipoda, Maeridae) in New Zealand - Kilgallen, Niamh M.; Ahyong, Shane T. (Zootaxa, 2011)
The New Zealand species of the amphipod crustacean genus Mallacoota are revised. Previous records of Mallacoota subcarinata (Haswell, 1879) from New Zealand are based on a new species, Mallacoota chiltoni sp. nov. and M. petriei (Thomson, 1882), which is re-established as valid based on a neotype. Mallocoota chiltoni apparently has a southern distribution in New Zealand, occurring only south of the Subtropical Convergence, whereas M. petriei ranges widely in both the north and south islands. A history of the genus Mallacoota in New Zealand is given.